Commentary: vitamin D supplementation in Crohn's disease. Issue 1 (18th December 2019) - Probert, Chris
Abstract : THIS IS A SPECIAL COMMENTARY ON " LOW EXPOSURE TO SUNLIGHT IS A RISK FACTOR FOR CROHN'S DISEASE " BY NERICH, V., JANTCHOU, P., BOUTRON‐RUAULT, M.‐C., MONNET, E., WEILL, A., VANBOCKSTAEL, V., AULELEY, G.‐R., BALAIRE, C., DUBOST, P., RICAN, S., ALLEMAND, H., AND CARBONNEL, F., ORIGINALLY PUBLISHED IN AP&T IN 2011. DOI:10.1111/J.1365-2036.2011.04601.x